Integrasi Kurikulum Berbasis Tarekat Syattariyah di Pondok Pesantren Nurul Yaqin Ringan-Ringan - Oktavia, Devi; Satria, Rengga (Lembaga Yasin AlSys, 2024)
The Syattariyah Order became well-known in the late 18th century, introduced in Sumatra by Abdur Rauf of Singkil, Aceh (1605-1693). One of his disciples, titled Sheikh Burhanuddin, brought it to Ulakan in the second half of the 17th century, and it continued to spread to various Islamic boarding schools in Minangkabau. This study aims to explore and analyze the process of integrating the curriculum based on the Syattariyah Order at Pondok Pesantren Nurul Yaqin Ringan-Ringan. The Syattariyah Order is one of the orders focused on teaching Sufism and Islamic spirituality. By integrating these teachings into the pesantren's curriculum, it is expected to shape students' character to be not only academically excellent but also to have strong spiritual and moral depth. The research method used is descriptive qualitative with a phenomenological approach. Data were collected through observations, in-depth interviews with the pesantren caretakers, teachers, and students, and document analysis related to the curriculum and teachings of the Syattariyah Order. The results of the study indicate that this curriculum integration is carried out through various activities such as regular religious lectures, recitation of wirid and dhikr, and other spiritual practices adapted to the teachings of the Syattariyah Order. In conclusion, the integration of the Syattariyah Order-based curriculum at Pondok Pesantren Nurul Yaqin Ringan-Ringan provides positive contributions to the spiritual and moral development of students, although it requires adjustments and deep understanding from all related parties. This research recommends further support from related institutions and training for teachers to strengthen the implementation of this curriculum.